Advancements in crop water modelling: algorithmic developments and parameter optimization strategies for sustainable agriculture: a review - Sulaiman, Ahmad S. S.; Wayayok, Aimrun; Aziz, Samsuzana A.; Yun, Wong Mui; Leifeng, Guo (University of Basrah, College of Agriculture, 2024)
This paper presents a review on algorithm development and crop water modelling with a focus on optimizing significant parameters related to crop factors, soil factors, and weather factors. The accurate representation and optimization of these parameters are crucial for reliable predictions and effective decision-making in agricultural practices. The objective of this review is to analyse the existing literature on algorithm development, parameter optimization techniques, and their application in crop water modelling, specifically emphasizing the importance of crop factors, soil factors, and weather factors. The review concludes with a discussion on the key findings and future directions in algorithm development and optimization for crop water modelling. It highlights potential research gaps and challenges that need to be addressed to improve the accuracy and efficiency of crop water modelling. The impact of optimized modelling approaches on sustainable agricultural practices and water management is also discussed. Overall, this comprehensive review provides valuable insights into the importance of algorithm development, optimization, and parameter selection in crop water modelling, specifically focusing on crop factors, soil factors, and weather factors.